Hydromechanical Coupling Characteristics of the Fractured Sandstone under Cyclic Loading-Unloading. (31st October 2020) - Zhang, Tong; Liu, Yang; Yang, Ke; Tang, Ming; Yu, Xiang; Yu, Fei
Abstract : The mechanical and hydraulic properties of rock mass play a crucial role in underground engineering. To study the effect of hydraulic pressure, confining pressure, and axial cyclic loading-unloading on variation of the deformation and permeability in fractured rock mass, the coupling triaxial experiment of sandstone was conducted. The concept of permeability recovery rate (PRR) and permeability enhancement reduction rate (PERR) was proposed to characterize the change in permeability. The results show that the permeability of fractured sandstone quadratically varies with the change of hydraulic pressure and confining stress. In detail, the permeability decreases with the decrease of hydraulic pressure and increases with the decrease of confining stress, respectively. Compared with the single-fracture permeability, the double-fracture permeability is more sensitive to the change of hydraulic pressure. Furthermore, the permeability of fractured sandstone is more dependent on the hydraulic pressure than the confining stress. With the performance of axial cyclic loading-unloading, the permeability spirals down, and both the axial and radial residual strains quadratically evolve. Following the first axial cyclic loading-unloading, an obvious deformation memory phenomenon characterized by a parallelogram shape in axial stress-strain curves was observed for the sandstone. The cumulative PRR of 85%-95% was maintained in double-fracture sandstone. On the contrary, a fluctuation of cumulative PRR characterized by "V shape" was observed for single-fracture sandstone. The enhancement effect of axial cyclic loading on the permeability was characterized by the decrease of PERR for double-fracture sandstone and increase of PERR with a greater gradient for single-fracture sandstone.